Interactive Multimedia Development in Learning English Vocabulary for Young Learners - Wardah Mawaddah Lubis; Dyah Setyowati Ciptaningrum; Bafirman Bafirman (STKIP Singkawang, 2025)
The aim of this study was to 1) examine the target and learning needs of grade four students; 2) develop interactive learning multimedia for learning English vocabulary for young learners; 3) explain the process of developing interactive multimedia; 4) reveal the interactive multimedia appropriateness to be used as a learning media. This study was design based research (DBR). The development model refers to Jolly & Bolitho in Tomlinson (2011) which consist of seven steps which modified into six steps. The data were collected through interview transcript and questionnaires consisting of students’ need analysis questionnaires; expert judgment questionnaires; students’ evaluation questionnaires. The data from the interview were analyzed descriptively. Meanwhile, the data collected using questionnaires were analyzed quantitatively with percentages and frequencies. There were six units of the developed multimedia. For its appropriateness, the media was validated by media expert and students. Based on the expert judgment questionnaires, the media was categorized as “very good” with the mean values of 3.6. The result of the students’ evaluation also showed that the product categorized as “very good” with the mean values 3.4. This means that the media is considered appropriate to be used as a learning media.